Analisis Performa Proses Enkripsi dan Dekripsi Menggunakan Algoritme AES-128 Pada Berbagai Format File - Rohbi Visdya Harris Chandra; Ari Kusyanti; Mahendra Data (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Every company has data that must be stored in digital form. Along with the development of the company, the data that needs to be stored will be more and more, so that the storage space needed will also be greater. In addition, data security factors also need to be considered. One method of securing data is by encrypting data. In the research conducted is an encryption algorithm analysis, which according to the results of the analysis shows that the AES algorithm shows an algorithm recommended as an algorithm to secure file usage. This study proposed an analysis of the AES encryption method. There are several parameters for testing the encryption method, namely encryption costs, computation time and testing several file formats encrypted and decrypted with file size references for document and image file formats, for audio and video file formats referring to the time duration, then from each file format selected two file extensions used for testing. Based on the results of the test shows that the AES encryption method provides good results for a number of file formats, AES-128 is able to encrypt files well even though it requires a long computing time in some of the file extensions tested. The time needed for the encryption and decryption process using the AES algorithm is affected by each different file size, the larger the file size used, the longer computation time needed.